A phase 3, randomized, controlled trial of Astodrimer 1% Gel for preventing recurrent bacterial vaginosis. (April 2021) - Schwebke, Jane R.; Carter, Belvia A.; Waldbaum, Arthur S.; Agnew, Kathy J.; Paull, Jeremy R.A.; Price, Clare F.; Castellarnau, Alex; McCloud, Philip; Kinghorn, George R.
Highlights: Recurrent bacterial vaginosis impacts on women and carries a high financial burden. Astodrimer 1% Gel was superior to placebo for prevention of recurrent BV. Astodrimer 1% Gel was well tolerated when used every second day for 16 weeks. Results support the use of Astodrimer 1% Gel for prevention of recurrent BV. Abstract: Objective: The objective of the study was to confirm the efficacy and safety of Astodrimer 1% Gel to prevent recurrence of bacterial vaginosis. Study design: 864 women with a diagnosis of bacterial vaginosis and a history of recurrent bacterial vaginosis were enrolled in North America and first received oral metronidazole (500 mg twice daily for 7 days). Women successfully treated with metronidazole were randomly assigned 1:1 to Astodrimer 1% Gel (N = 295) or placebo (N = 291) at a dose of 5 g vaginally every second day for 16 weeks, and followed for a further 12 weeks off-treatment. The primary endpoint was recurrence of bacterial vaginosis (presence of ≥3 Amsel criteria) at or by Week 16. Secondary endpoints included time to recurrence, and recurrence of subject-reported symptoms. Adverse events were monitored throughout the study. Results: Astodrimer 1% Gel was superior to placebo for the primary and many secondary efficacy measures. At or by Week 16, bacterial vaginosis recurred in 44.2 % (130/294) of women receiving astodrimer and 54.3 % (158/291) receiving placebo ( P = .015). Time to recurrence of bacterial vaginosis was significantly longer for women receiving astodrimer compared with placebo (Kaplan-Meier survival curves, P = .007). Recurrence of subject-reported symptoms at or by Week 16 was also significantly lower in the astodrimer arm compared with placebo (vaginal odor and/or discharge, 27.9 % [75/269] vs 40.6 % [108/266], P = .002). A significantly lower proportion of patients receiving astodrimer compared with placebo had recurrence of bacterial vaginosis at or by Week 16 by other secondary measures, including individual Amsel criteria (vaginal discharge and clue cells) and Nugent score 7−10. Recurrence of subject-reported vaginal odor and/or discharge was significantly lower in the astodrimer arm compared with placebo up to 8 weeks after cessation of therapy (36.1 % [97/269] vs 45.5 % [121/266], P = .027). Adverse events were infrequent, and rates were generally similar between placebo and astodrimer groups. Vulvovaginal candidiasis and urinary tract infection occurred more often in women receiving astodrimer. Conclusions: Astodrimer 1% Gel, administered every second day for 16 weeks, was effective and superior to placebo for prevention of recurrent bacterial vaginosis in women with a history of recurrent BV, and was well-tolerated.